Implementation of land sustainable food agriculture protection policy in Sukabumi City - Rahmah, Laila; Sampurna, Rizki Hegia; Nur, Tuah (Universitas Merdeka Malang, 2024)
This study aims to analyze the policy implementation of sustainable food agricultural land (PLP2B) protection in the City of Sukabumi. PLP2B is a government effort to protect productive agricultural land that has decreased due to conversion due to the growth of urban areas. Therefore, sustainable food agricultural land protection must be carried out optimally by applicable policies. This research uses a qualitative method with a descriptive approach and data collection techniques through field observations, interviews, and documentation. Informants were determined using a non-probability sampling technique with a snowball sampling method. This research uses the theory of Van Meter van Horn (1975). The results of this study indicate that the implementation of sustainable food agricultural land protection policies in the city of Sukabumi is still not running optimally due to several obstacles, such as budget constraints, the economic value of agriculture, which is relatively small, and the depreciation of agricultural land which is changing functions every year. However, improvement efforts continue to improve the quality of the sustainable food agricultural land protection policy (PLP2B) in Sukabumi City.